2002
DOI: 10.1093/jnen/61.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Hippocampal Cholinergic Neurostimulating Peptide Precursor Protein mRNA in the Hippocampus in Alzheimer Disease

Abstract: Hippocampal cholinergic neurostimulating peptide (HCNP) is involved in the phenotype development of the septo-hippocampal system. HCNP precursor protein (HCNP-pp) is known to interact with other molecules including phosphatidylethanolamine and Raf-1 kinase, and is also known as phosphatidylethanolamine-binding protein and raf kinase-inhibitory protein. To assess whether HCNP-pp is involved in the pathogenesis of Alzheimer disease (AD), the expression levels of its mRNA in the hippocampus of autopsy brains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 46 publications
4
58
0
Order By: Relevance
“…63 Consistent with a potential role of HCNP in AD, levels of pebp1 mRNA are suppressed in the CA1 region of the hippocampi of clinically late-onset AD patients relative to nondemented controls. 64 Given previous evidence that shows that AD pathologies are localized in the CA1 region and there is loss of cholinergic fibers innervating the hippocampus, this study suggests that reduced expression of HCNP may contribute to the pathogenesis of AD. In comparison, earlier work showed that the cerebrospinal fluid (CSF) of some early-onset, but not late-onset, AD patients exhibits high levels of HCNP relative to non-AD patients.…”
Section: Rkip and Association With Alzheimer's Diseasesupporting
confidence: 63%
“…63 Consistent with a potential role of HCNP in AD, levels of pebp1 mRNA are suppressed in the CA1 region of the hippocampi of clinically late-onset AD patients relative to nondemented controls. 64 Given previous evidence that shows that AD pathologies are localized in the CA1 region and there is loss of cholinergic fibers innervating the hippocampus, this study suggests that reduced expression of HCNP may contribute to the pathogenesis of AD. In comparison, earlier work showed that the cerebrospinal fluid (CSF) of some early-onset, but not late-onset, AD patients exhibits high levels of HCNP relative to non-AD patients.…”
Section: Rkip and Association With Alzheimer's Diseasesupporting
confidence: 63%
“…The role of RKIP-1 in AD emerges through its diminished expression in affected neurons [14]. An inverse correlation between the severity of AD and the RKIP-1 level in human and mouse brains has been reported [14,24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, RKIP has a variety of physiological functions in brain, including its function in the synaptic plasticity and circadian clock [3]. As a precursor protein of hippocampal cholinergic neurons, RKIP is important to synthesis acetylcholine and develop septal cholinergic neurons for learning and memory [4]. Furthmore, RKIP expression disorders can lead to diabetic nephropathy and Alzheimer’s disease [5].…”
Section: Introductionmentioning
confidence: 99%